2020
DOI: 10.1055/s-0040-1716404
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Microvascular Complications in Autologous Breast Reconstruction: The Effects of Resident Training on Microsurgical Outcomes

Abstract: Background Academic medical centers with large volumes of autologous breast reconstruction afford residents hand-on educational experience in microsurgical techniques. We present our experience with autologous reconstruction (deep inferior epigastric perforators, profunda artery perforator, lumbar artery perforator, bipedicled, and stacked) where a supervised trainee completed the microvascular anastomosis. Methods Retrospective chart review was performed on 413 flaps (190 patients) with microvascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…This finding also confirms Teotia and colleagues findings that resident progression does not affect operative duration. 23 Therefore, improvements in operative time can be attributed to the efficiency of the primary microsurgeon in both technique and decision making.…”
Section: Discussionmentioning
confidence: 99%
“…This finding also confirms Teotia and colleagues findings that resident progression does not affect operative duration. 23 Therefore, improvements in operative time can be attributed to the efficiency of the primary microsurgeon in both technique and decision making.…”
Section: Discussionmentioning
confidence: 99%
“…7 However, no differences in operative time, complication rate, or flap losses based on resident training level were determined. 7 Our finding that presence of a junior resident, regardless of total resident experience years present, increases risk of anastomotic failure suggests that even with several experienced hands in the room, teaching early-stage trainees during a case may necessitate greater attention during key steps of the anastomosis, a highly complex endeavor. 10 Within the same postgraduate year, academic quarter did not affect rates of anastomotic failure.…”
Section: Discussionmentioning
confidence: 99%
“…Teotia et al found that up to 16% of autologous free flaps at an academic medical center required at least one intraoperative microvascular revision for venous congestion, arterial thrombosis, kinked vessels, leakage, or vessel collapse. 7 Despite potential anastomotic complications, a paucity of studies have examined factors associated with intraoperative anastomotic complications during DIEP flaps.…”
mentioning
confidence: 99%
“…However, our experience and reported literature shows that there are no impacts on operative time or intraoperative complications based on trainee level. 33 As such, it may be included in microvascular surgery to gain real-life operative experience and repetition while having no negative financial impact on the patients or institution utilizing an ERAS protocol.…”
Section: Discussionmentioning
confidence: 99%